2019
DOI: 10.1101/520643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geometric control of frequency modulation of cAMP oscillations due to Ca2+-bursts in dendritic spines

Abstract: The spatiotemporal regulation of cAMP and its dynamic interactions with other second messengers such as calcium are critical features of signaling specificity required for neuronal development and connectivity. cAMP is known to contribute to long-term potentiation and memory formation by controlling the formation and regulation of dendritic spines. Despite the recent advances in biosensing techniques for monitoring spatiotemporal cAMP dynamics, the underlying molecular mechanisms that attribute to the subcellu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…These enzymes can also be localized by A-kinase anchoring proteins (AKAPs) and change cAMP/PKA dynamics further [83][84][85]. The effect of spine size and enzyme localizations are considered in a companion study [23]. Figure 7: The frequency control in the modeled cAMP/PKA pathway from calcium stimulation through PKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes can also be localized by A-kinase anchoring proteins (AKAPs) and change cAMP/PKA dynamics further [83][84][85]. The effect of spine size and enzyme localizations are considered in a companion study [23]. Figure 7: The frequency control in the modeled cAMP/PKA pathway from calcium stimulation through PKA.…”
Section: Discussionmentioning
confidence: 99%
“…All the biochemical species including the membranebound ones are well-mixed across this compartment. A separate spatial model is presented in [23].…”
Section: Model Assumptionsmentioning
confidence: 99%
“…For example, fluorescence experiments have shown that the dendritic spine necks act as a diffusion barrier to calcium ions, preventing ions from entering the dendritic shaft [59]. Complementary to this and other experiments, various physical models solving reaction-diffusion equations in idealized geometries have been developed to further interrogate the structure-function relationships [41,53,[64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…All the biochemical species, including the membrane-bound ones, are well-mixed across this compartment. A separate spatial model is presented in (62).…”
Section: Compartment Sizementioning
confidence: 99%